2016
DOI: 10.3390/s16071035
|View full text |Cite
|
Sign up to set email alerts
|

Policy 2.0 Platform for Mobile Sensing and Incentivized Targeted Shifts in Mobility Behavior

Abstract: Sustainable mobility and smart mobility management play important roles in achieving smart cities' goals. In this context we investigate the role of smartphones as mobility behavior sensors and evaluate the responsivity of different attitudinal profiles towards personalized route suggestion incentives delivered via mobile phones. The empirical results are based on mobile sensed data collected from more than 3400 people's real life over a period of six months. The findings show which user profiles are most like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
1
33
0
2
Order By: Relevance
“…In this context, the present contribution formulates a pioneering proposal, by drawing a Policy 2.0 concept and exploring the real-life use case where Policy 2.0 platform is used in supporting sustainable mobility related planning. The idea of Policy 2.0 platform for smart cities has been already discussed (but only in a preliminary formation) in Semanjski et al [33]. In this paper, the authors significantly extend their previous contribution by detailing how data driven insights can contribute to decision making and smart city's planning processes based on a Policy 2.0 platform.…”
Section: Figuresupporting
confidence: 54%
See 2 more Smart Citations
“…In this context, the present contribution formulates a pioneering proposal, by drawing a Policy 2.0 concept and exploring the real-life use case where Policy 2.0 platform is used in supporting sustainable mobility related planning. The idea of Policy 2.0 platform for smart cities has been already discussed (but only in a preliminary formation) in Semanjski et al [33]. In this paper, the authors significantly extend their previous contribution by detailing how data driven insights can contribute to decision making and smart city's planning processes based on a Policy 2.0 platform.…”
Section: Figuresupporting
confidence: 54%
“…The acceptability of this incentive varied among different homogeneous subgroups of users, reaching up to 18% for Carfree Choosers [33]. Compared with results from literature where traditional communication means were used to familiarize transport system users with available alternatives [77] these results are on average twice higher.…”
Section: Behavioural Change Evaluationmentioning
confidence: 64%
See 1 more Smart Citation
“…As a consequence, current systems measure air pollution at a very low spatial resolution, e.g., only 22 stations covering a 50 × 50 km 2 (113 km 2 per station) in Beijing, 14 stations covering 1572 km 2 (112 km 2 per station) in London, and 61 stations (221 km 2 per station) in Flanders, Belgium. Researchers have also placed pollution sensors to assess the personal exposure to air pollution in places of interest [6][7][8][9], such as major roads with heavy traffic and industrial sites. Measurements obtained at these stations or locations can only reflect the air pollution level there or in small areas around there.…”
Section: Introductionmentioning
confidence: 99%
“…In order to balance the need for personal mobility and increase the sustainability of mobility systems as a whole, much has been done in promoting active transport modes such as biking and walking. However, overall results are still unsatisfactory [2], and results seem to be limited, as many are not motivated by topics such as fitness or environment, and are continuing to use personal vehicles for their mobility needs even when other feasible solutions exist [3]. Secondly, studies have shown that personal vehicles are used on average around an hour per day [4,5].…”
Section: Introductionmentioning
confidence: 99%